KALAVA FISHERIES OF PULLUVILA VILLAGE - Mohan, Madan (Indian Journal of Fisheries, 2011)
An account of the Kalava fishery of PuUuvila village, south of Trivandrum in Kerala State, during 1980 and 81 is given in this paper. Species composition of the catches, location of the fishing grounds, estimated catches during both the years and economics of the fishery are discussed.